Examination of the Impact of Terms of Trade on Investment in Economy of Iran - Mostafa Karimzadeh; Khadijeh Nasrollahi; Saeed Samadi; Rahim Dallai Esfahani (Faslnāmah-i Pizhūhish/Nāmah-i Iqtisādī, 2011)
The main idea of this study is examination of the Impact of Terms of Trade on Investment by Johnsen-Juselius cointegration technique for Economy of Iran in (1971-2006). For this aim, we specify investment function according the present value criteria and neoclassic theory. Our model includes gross domestic production, price index, interest rate and terms of trade. We use Johnsen-Juselius cointegration technique for estimation of this model. The result of econometric estimation has indicated a long run relationship among investment, gross domestic production, price index, interest rate and terms of trade. Our result showed GDP, price index and terms of trade have direct effect and interest rate has inverse effect on investment.